Factors Influencing Seller’s Satisfaction of E-Commerce Platforms (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The rapid growth of the online marketplace sector has transformed the way sellers operate their businesses in the digital age. The choice of online marketplace platform is a strategic decision as it directly influences market reach, operational efficiency and seller satisfaction. This study aims to analyse the influence of promotions, transaction costs, delivery services, and vendor support on seller satisfaction when selecting an online marketplace platform. The study employs a quantitative approach using a survey method involving 100 sellers operating in the Central Java region. Data were collected via a structured questionnaire and analysed using Partial Least Squares-based Structural Equation Modelling (SEM-PLS). The results indicate that promotions, transaction costs, delivery services, and vendor support have a positive influence on seller satisfaction. Among these four factors, vendor support has the most significant influence on seller satisfaction when using online marketplace platforms. These findings suggest that the technical support and services provided by platform operators play a crucial role in enhancing seller satisfaction and the continued use of the platform by sellers.